Medical Misadventure and Accident Compensation in New Zealand: An Incentives-Based Analysis - Howell, Bronwyn (Victoria University of Wellington Law Review, 2004)
This article discusses the role of incentives in reducing the occurrence of medical misadventure. The author argues that appropriate incentives may induce the practice of insuring appropriate levels of precaution by sharing the costs of insufficient levels of precaution between those with the power to exert clinical precaution (practitioners) and monitor and enforce its exertion (administrative agencies), and the victims who otherwise bear the costs of inadequate levels of precaution being taken. The respective ability of tortbased and nofault systems to achieve this level of care is discussed, and then applied in the New Zealand ACC situation. The author concludes that from the available evidence, incentives associated with a faultbased system are extremely difficult, if not impossible, to replicate in a nofault system. This is even harder to achieve when public funding of both the ACC and health systems further reduces the incentives potentially available when individuals must meet the cost of their own treatment and liability insurance.